Onion Setsʼ Yield and Quality as Affected by Seed Rate of Two Onion (Allium cepa L.) Cultivars (University of Khartoum Journal of Agricultural Sciences, 2021)
Onion bulb crop production using sets as planting material has been increasing for the last decade in response to the high demand and because of their high yielding capacity and adaptability to the continuously changing growing environment. The objective of this experiment, therefore, was to investigate the effect of seed rate on the yield and quality of onion setsas a highly demanded planting material. Treatments comprised two cultivars (Kamlin and Saggai) and three seed rates (60,120 and 180 kg/ha.). They were arranged in a split plot design with three replications. Cultivars were in themain plots and seed rates in the subplots. Average set weight and total set yield decreased with increasing seed rate. The highest yield was produced at 60 kg/ha and the lowest at 180 kg/ha. seed rate. Yield of the set size distribution categories was significantly affected by seed rate; seed rate of 120kg/ha resulted in the highest yield of medium set (best for production ofbulbs), followed by 60 and 180 kg/ha. Yield of set size categories decreased with increasing seed rate except for small set size category which significantly increased with increasing seed rate
Keywords: common onion; Allium cepa L.; onion set; seed rate